Hubungan Tingkat Spritualitas DanPenerimaan Diri Terhadap Kualitas HidupOrang Dengan HIV/AIDS (ODHA) - Wildan Nafi’ah; Erna Melastuti (Pusat Riset dan Inovasi Nasional, 2025)
Background: The level of spirituality in people living with HIV/AIDS plays a critical role in their journey toward self-acceptance. Spirituality often serves as a bridge between despair and hope, offering individuals the strength to surrender to the Creator in search of recovery from their suffering. Moreover, spirituality can provide a sense of inner peace, contributing positively to the quality of life for those affected. As individuals confront the challenges of living with HIV/AIDS, spirituality and self-acceptance can be vital components in coping with the illness and improving their overall well-being.Objective: This study aims to explore the relationship between the level of spirituality, self-acceptance, and the quality of life of people living with HIV/AIDS. Understanding these relationships can inform healthcare professionals on how to support patients in their mental and emotional healing.Method: This non-experimental quantitative study used a correlational approach. Data were collected through questionnaires distributed to 146 people living with HIV/AIDS at the Poncol Health Center in Semarang. Respondents were selected randomly based on predetermined inclusion and exclusion criteria. The data were analyzed using the gamma test to examine the relationships between the variables.Results: The study found a significant relationship between spirituality and quality of life (p = 0.021), as well as between self-acceptance and stress levels (p = 0.027). There was a clear correlation between spirituality, self-acceptance, and improved quality of life among HIV/AIDS patients.Conclusion: This study demonstrates the significant role of spirituality and self-acceptance in enhancing the quality of life for people living with HIV/AIDS.Suggestion: For nursing science, this research emphasizes the importance of integrating spirituality and self-acceptance into care strategies, enabling healthcare providers to offer more holistic and effective interventions for patients.